2014
DOI: 10.1128/jb.01299-13
|View full text |Cite
|
Sign up to set email alerts
|

Calvin Cycle Mutants of Photoheterotrophic Purple Nonsulfur Bacteria Fail To Grow Due to an Electron Imbalance Rather than Toxic Metabolite Accumulation

Abstract: Purple nonsulfur bacteria grow photoheterotrophically by using light for energy and organic compounds for carbon and electrons. Disrupting the activity of the CO 2 -fixing Calvin cycle enzyme, ribulose 1,5-bisphosphate carboxylase (RubisCO) However, we also demonstrate that Rs. rubrum and Rp. palustris Calvin cycle phosphoribulokinase mutants that cannot produce RuBP cannot grow photoheterotrophically on succinate unless an electron acceptor is provided or H 2 production is permitted. Thus, the Calvin cycle is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 34 publications
(47 reference statements)
2
36
0
Order By: Relevance
“…). These findings are in agreement with previous observation under photoheterotrophic conditions in the presence of organic carbon, such as acetate, that suggested that the CBB cycle is involved in the maintenance of the redox balance in the cell, but not in CO 2 fixation (McKinlay and Harwood, 2010; 2011; Gordon and McKinlay, ).…”
Section: Resultssupporting
confidence: 93%
“…). These findings are in agreement with previous observation under photoheterotrophic conditions in the presence of organic carbon, such as acetate, that suggested that the CBB cycle is involved in the maintenance of the redox balance in the cell, but not in CO 2 fixation (McKinlay and Harwood, 2010; 2011; Gordon and McKinlay, ).…”
Section: Resultssupporting
confidence: 93%
“…). Nase functions in both nitrogen acquisition and electron balance, while the primary role of CO 2 fixation during photoheterotrophic growth is as an electron sink (Hallenbeck et al ., ; Falcone and Tabita, ; Hädicke et al ., ; Farmer et al ., ; Gordon and McKinlay, ). Total electron flux through Nase and Rubisco increases with the growth rate for the wild type, Mo‐Nase and V‐Nase strains, but is always high for the Fe‐Nase strain (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1, Arrow E), such that electrons from the organic substrate are fully allocated between biomass, H 2 and CO 2 . Under these conditions, Nase is important both for nutrient acquisition and as an electron sink (Muller, 1933;Hillmer and Gest, 1977;Harwood, 2010a, 2011;Farmer et al, 2014;Gordon and McKinlay, 2014;McCully and McKinlay, 2016). To determine how simultaneous nitrogen acquisition and electron balancing constraints influence growth based on each Nase isoform, we cultured wild type R. palustris and mutant strains known to utilize only a single isoform (hereafter Mo-Nase, V-Nase and Fe-Nase strains, Oda et al, 2005) in diazotrophic photoheterotrophic media with organic substrates of varying oxidation states and assimilation pathways (Table 1) and measured growth, N 2 and CO 2 fixation, H 2 production, biomass composition and global protein abundance patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Cultures were grown in 10-mL volumes in 27-mL anaerobic test tubes or in 60-mL volumes in 160-mL serum vials at 30°C. Media were made anaerobic by bubbling with either N 2 or Ar and sealed as previously described (23). Test tubes were laid flat, and serum vials were left upright.…”
Section: Methodsmentioning
confidence: 99%